INNOVATIVE ENTREPRENEURSHIP IN CONDITIONS OF LIMITATIONS AND CRISIS - GONTAREVA, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The report of the World Intellectual Property Organization (WJPO) for 2020 statistically confirms the connection between the global financial crises and falling spending on research and development. The purpose of this article is to systematize and content analysis of financial and information-cognitive limitations of the emergence and formation of innovative small businesses in crisis and post-crisis periods. The study shows that, first, the investment of the business sector in research and development is more stable than in government agencies. This is due to the fact that during the crisis the state is forced to expand the general support of the population and the most affected part of the business, including small businesses. Second, investment in research and development and innovation are the basis for further economic recovery and growth. Third, before the COVID-19 pandemic, the global economy had not yet fully recovered from the 2008 financial crisis. This affects the innovative activity of small businesses. In the face of ongoing crises, small innovative enterprises face different types of constraints and barriers. In particular, it is the reduction of venture capital and the share of the state in the financing of research and development, as well as the transfer of knowledge on high-tech technologies. The government's solution to the problem with the help of industrial parks requires a more detailed technological foresight analysis. In developed countries, in addition to the expert opinions of the scientific, business and political communities, the population is encouraged, taking into account their views on technology prospects and the state of the environment. Accordingly, sufficient technological literacy and cognitive ability of the population is assumed. Technological literacy of entrepreneurs who are going to use high-tech and especially breakthrough technologies must be above the amateur level. In the future, it is planned to conduct a content analysis of existing technological foresight forecasts.
Keywords: innovative small enterprises; crisis phenomena; barriers to innovative development; industrial parks; technological literacy